How Residents' Attitudes to Tourists and Tourism Affect Their Pro-tourism Behaviours: The Moderating Role of Chinese Traditionality - Shen, Ke; Yang, Jian; Geng, Chuan (Frontiers in Psychology, 2022)
Although sufficient attention has been paid to residents' attitudes to tourism in previous studies, few studies have used residents' attitudes to tourists and tourism simultaneously to explain their support for tourism. This study fills this gap by examining the effect of place image and host–tourist interactions on residents' attitudes to tourists and tourism, respectively, and their consequent reactions by considering the moderating effect of Chinese traditionality. The proposed model is tested using data from 357 residents living in Huangshan, a fifth-tier city in China. Results demonstrate that attitudes to tourism and host-tourists interaction positively affect their pro-tourism behaviours. Moreover, attitudes to tourism mediate place the image's, host–tourists interaction's and attitudes to tourists' respective relationships with pro-tourism behaviours. Furthermore, the higher the Chinese traditionality of residents, the stronger the influence of their attitudes to tourism on pro-tourism behaviours. However, the relationship of place image and attitudes of residents towards tourists with pro-tourism behaviours are not supported. Findings offer critical implications for planners, practitioners and interested researchers.